Towards the XXI National Sports Week in 2024: the extent of the psychological profile of North Sumatra PON Athletes - Nasuka; Sulaiman; Hermawan Pamot Raharjo; Eka Abdurrahman (Universitas Negeri Semarang, 2024)
This research is aimed at identifying the psychological profile of North Sumatra PON athletes. Apart from that, each psychological aspect of North Sumatra PON athletes will be analyzed for the condition of each psychological aspect along with the distribution of athletes and their percentages. The method used in this research is a survey method with an ex post facto research design. The population in this study is North Sumatra PON athletes who will be prepared for the XXI Aceh-North Sumatra PON 2024. The sampling technique in this study uses purposive sampling with the criteria of North Sumatra PON Athletes who have carried out the North Sumatra Province training camp in 2024. Based on that, So the research sample of sports athletes was obtained, namely; Petanque, Kabaddi, Athletics, Volleyball, Futsal, Basketball, Pencaksilat totaling 101 athletes. Data collection used The Psychological Skills Inventory for Sports (PSIS) questionnaire. The research results show that the psychological profile of North Sumatra PON athletes heading towards PON XXI 2024 is generally in good condition.